Comparison of single-line rate for dedicated protection on WDM optical network topologies - Suthaharan, S.; Samarakkody, D.; Perera, W.A.S.C. (IEEE International Conference on Information and Automation for Sustainability (ICIAfS), 2016)
Wavelength division multiplexing (WDM) divides the huge bandwidth available on a fiber into several non-overlapping wavelength channels and enables data transmission over these channels simultaneously. Failure of the optical fiber causes loss of huge amount of data which can interrupt communication. There are several approaches to ensure network survivability. In survivability, we consider dedicated protection in this paper in which backup paths are configured at the time of establishing connections. If a primary path is failed, the traffic is rerouted through backup path with a short recovery time. In this paper, we investigate the performance by calculating the spectrum efficiency variation for dedicated protection in WDM networks. Spectrum efficiency is calculated by dividing the total traffic bit rate by the total spectrum used. In this paper, we carry out the investigation with detailed simulation experiments on different single-line rate (SLR) scenarios such as 100 Gbps, 400 Gbps, and 1Tbps. In addition, this paper focuses on four standard network topologies which consist of different number of links to identify how the spectrum efficiency varies for each network. Our findings are as follows. (1) Spectrum efficiency for each SLR are almost similar and comparable in all the network topologies. (2) Unlike network topology with low number of links, the spectrum efficiency for network topology with high number of links are higher, therefore, the spectrum efficiency increases when the number of links are increased. (3) The spectrum efficiency is lower when the number of primary links is higher even though in all the network topologies.
Keywords: wavelength division multiplexing; spectrum efficiency; dedicated protectio; single line rate